SOCIALIZATION OF ADMINISTRATIVE RECORDS AND FINANCIAL MANAGEMENT OF VILLAGE-OWNED ENTERPRISES IN PUKDALE VILLAGE - Alexander Wewo, Jeremia (LPPM Univ. Ibn Khaldun Bogor, 2024)
This activity was motivated by the fact that administrative records and financial management in Village-Owned Enterprises had not been properly and properly organized. This service aims to provide an explanation of administrative recording and financial management of village-owned enterprises (BUMDes) located in Pukdale Village. The method used is socialization, namely the service provider provides material and then has a question and answer discussion. The results of the service and discussion found that administrative recording activities consist of expeditions in the form of activities to record any information sent or received, both for internal and external purposes and archiving is a process of systematically organizing information storage so that it can be easily and quickly found if needed while financial management includes planning, organizing, implementing, and controlling financial activities. The suggestion given in this service is that the socialization that has been delivered by the dedication should be carried out by all village officials so as to create a quality pattern of administrative recording and financial management.